Re-evaluating Gandhi: Swaraj and Swadeshi in ‘Environmental’ Activism - Cox, Peter (Journal for the study of religion, nature and culture, 2004)
Gandhian contributions to the development of the green movement have been generally under-explored. This article seeks to re-examine key Gandhian themes in order to indicate their potential contribution to some contemporary debates. The emphasis on place-centred knowledge, tempered by a ‘post-relativistic ethic’, is highlighted as a valuable resource for interpreting contemporary ‘environmental’ activism. It is suggested that such a framework can provide grounds for further explorations beyond the limitations of the foundationalism-relativism debate. The Gandhian emphasis on swaraj and swadeshi also open considerable potential to link to wider debates on the nature of liberation, particularly in the context of post-colonial theory.